2016
DOI: 10.1002/btpr.2404
|View full text |Cite
|
Sign up to set email alerts
|

Affinity chromatography matrices for depletion and purification of casein glycomacropeptide from bovine whey

Abstract: Casein glycomacropeptide (CMP) is a 64- amino acid peptide found in cheese whey, which is released after κ-casein specific cleavage by chymosin. CMP lacks aromatic amino acids, a characteristic that makes it usable as a nutritional supplement for people with phenylketonuria. CMP consists of two nonglycosylated isoforms (aCMP A and aCMP B) and its different glycosylated forms (gCMP A and gCMP B). The most predominant carbohydrate of gCMP is N-acetylneuraminic acid (sialic acid). Here, we developed a CMP purific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Further, the separation of milk proteins/peptides has been based on PAGE [90] and on chromatographic separations [84], such as SEC [13], IEC [13,91], and affinity chromatography [92]. However, analytical separation methods, such as capillary HPLC (especially RP-HPLC) and CE, are very efficient and sensitive for milk proteins/peptides purification, and various techniques have been developed over years [84].…”
Section: Recent Advances In Separation Of Milk Bioactive Proteins/pep...mentioning
confidence: 99%
“…Further, the separation of milk proteins/peptides has been based on PAGE [90] and on chromatographic separations [84], such as SEC [13], IEC [13,91], and affinity chromatography [92]. However, analytical separation methods, such as capillary HPLC (especially RP-HPLC) and CE, are very efficient and sensitive for milk proteins/peptides purification, and various techniques have been developed over years [84].…”
Section: Recent Advances In Separation Of Milk Bioactive Proteins/pep...mentioning
confidence: 99%
“…GMP is therefore a 64-amino acid peptide, present exclusively in whey cheese, released after the specific cleavage of κ-casein by chymosin; consists of two non-glycosylated isoforms (aGMP A and aGMP B) and their different glycosylated forms (gGMP A and gGMP B), the most predominant carbohydrate of gGMP being N-acetylneuraminic acid (sialic acid) [9]. It should be noted that some psychotropical microorganisms (especially Pseudomonas fluorescens)…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that GMP helps the production of cytokines, regulating immune system interactions [11], is an immunomodulator that has an intestinal anti-inflammatory effect in rats with colitis type I [12] [13] [14], has gastric inhibitory activity [15] and is used for the nutritional management of phenylketonuria in humans [16] [17] [18], has a gastric inhibitory activity, because it lacks aromatic amino acids, making it usable as a nutritional supplement for these people [9]. Studies also show that GMP has anti-inflammatory, prebiotic and immunomodulatory effects, including for atopic dermatitis in humans [19].…”
Section: Introductionmentioning
confidence: 99%